Utilization of Social Media on Income of Fishery Products Distribution Businesses In Cilacap Regency During the Covid-19 Pandemic - Putranto, Yogi; Sudarmo, Agnes Puspitasari; Patanda, Mercy (Journal Omni-Akuatika, 2022)
Product marketing during the Covid-19 pandemic has changed. During this pandemic, marketing fishery products through social media is a solution and innovative step towards increasing income. This purposes of this study were to determine the type of social media used and the effect of the use of social media on the income of fishery product distribution business actors in Cilacap Regency. This study used purposive random sampling data collection techniques at Fish Auction Places (Tempat Pelelangan Ikan-TPI) Lengkong and Menganti Kisik Cilacap Regency with a sample of 30 respondents with 15 respondents each TPI. The analytical method used in this research is descriptive, SWOT analysis and scoring system. The results revealed that WhatsApps was the most widely used social media and was considered the most effective by respondents in marketing fishery products both at TPI Lengkong (60%) and TPI Menganti Kisik (66.7%). The study indicated that fishery product distribution business actors in Cilacap Regency consider that social media has an effect on increasing income at TPI Lengkong (46.7%) while at TPI Menganti Kisik (53.3%). This study recommends that stakeholders take an active role in opening up market share for fishery products, so that wider export opportunities for traditional fishery products could penetrate international market.Keywords: social media, distribution of fishery products, Cilacap, Covid 19 pandemic